2015
DOI: 10.1097/md.0000000000001945
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Epstein–Barr Viral Deoxyribonucleic Acid Predicts Worse Outcomes in Pediatric Nonmetastatic Nasopharyngeal Carcinoma Patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Pretreatment pEBV-DNA is an important biomarker to predict survival and guide treatment for adults with NPC ( 20 , 21 ). We demonstrated a similar role of pEBV-DNA in survival prediction in CaNPC, which agreed with the result of a previous study ( 16 ). An observational study by Shen et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Pretreatment pEBV-DNA is an important biomarker to predict survival and guide treatment for adults with NPC ( 20 , 21 ). We demonstrated a similar role of pEBV-DNA in survival prediction in CaNPC, which agreed with the result of a previous study ( 16 ). An observational study by Shen et al.…”
Section: Discussionsupporting
confidence: 92%
“…showed that the pretreatment pEBV-DNA load was an independent prognostic indicator for DMFS and OS in pediatric patients with NPC. In terms of overall survival, the cutoff value of pretreatment pEBV-DNA = 7,500 copies/ml was suggested for CaNPC in a retrospective analysis by Shen et al., which was also used in the present study ( 16 ). The difference in survival associated with pretreatment pEBV-DNA suggested that the treatment intensity of patients with different pretreatment pEBV-DNA levels could be individualized, which has been explored in adults with NPC ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the results of Lin et al, who observed similar values of EBV DNA VL for stages III and IV . On the contrary, different results to our and Lin et al were presented by Shen et al's study, in which the median pretreatment concentrations of EBV DNA were significantly higher in patients with stage IV than in those with stage III …”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, studies that explore whether treatment outcomes can be predicted by pretreatment levels of plasma EBV DNA in young NPC patients are rare. Although one retrospective study (15) has reported that plasma EBV DNA predicts worse outcomes in pediatric nonmetastatic NPC patients, the findings were based on a relatively small sample size without using uniform IMRT technique.…”
Section: Introductionmentioning
confidence: 99%